Energy efficiency improvement of an unbalanced electrical distribution system based on the conservative voltage reduction in tandem with the optical capacitors placement and sizing / Muhd Azri Abdul Razak - Abdul Razak, Muhd Azri (2015)
Energy efficiency can be achieved by means of minimizing the power losses with an adequate amount of energy utilized in an electrical distribution system. In this thesis, a detail analysis of energy efficiency of an electrical distribution system has been performed with an implementation of the conservative voltage reduction (CVR), and the optimal capacitor placement and sizing (OCPS). The differential evolution particle swarm optimization (DEPSO) is used to determine optimal location and sizing for the capacitors which in turn will improve the energy efficiency via energy consumption and power losses minimization. The pre-selection of busbar or locations is performed either based on the power-loss-index (PLI), randomly pre-selected location (RPL), or fixed pre-selected location (FPL). The DEPSO is designed based on the amalgamation of particle swarm optimization (PSO) and differential evolution (DE) that serves as a new mutation technique responsible to provide a new population with improved sizing and location of capacitors. The total cost of power losses, energy consumption and capacitor installation are the components considered in the objective and fitness functions of the proposed optimization technique. Voltage magnitude limit, total harmonic distortion (THD) limit, power factor limit and capacitor size limit are the parameters considered as the constraints for the proposed of optimization technique. Further improvement of energy efficiency is attained through CVR perpetrated by changing the transformer tap setting to reduce and then retain the voltage magnitude at a certain level whilst ensuring stability of the electrical distribution system. In this study, the proposed technique of DEPSO developed in MATLAB® will hand over the solution of capacitor locations, size as well as transformer tap position to the SIMULINK® software. Later, the SIMULINK® software will perform the load flow solution and pass the results to MATLAB® software to be analyzed. Effectiveness of the proposed methods used to improve the energy efficiency has been verified through several case studies and the results are obtained from the test systems of IEEE 13-bus unbalanced electrical distribution system and also the pragmatic electrical distribution system of Sultan Salahuddin Abdul Aziz Shah (SSAAS) building in Shah Alam, Selangor.